Development of in vitro technologies for clonal propagation of estate crops - Tahardi J S (Buletin Bioteknologi Perkebunan, 1994)
One of the major constraints in plantation development lies in the provision of superior planting materials. Conventional methods of vegetative propagation of estate crops by budding, budgrafting and leaf-node cutting can not meet the ever increasing demands of the fast-expanding plantation industry. In vitro technology is envisaged to provide a viable alternative for efficient mass production of high-quality planting materials. Micropropagation technologies for rubber, oil palm, coffee, cocoa and tea have been developed at the Indonesian Biotechnology Research Institute for Estate Crops (IBRIEC). The progress achieved to date in the regeneration and cloning of these tree crops is highlighted in this paper
Source Year: 1995
Keywords: Estate crops; Hevea; In vitro technology; Micropropagation; Plantation industry